2013
DOI: 10.7883/yoken.66.201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Escherichia coli O157:H7 Outbreak Strain Whose Shiga Toxin 2 Gene Is Inactivated by IS1203v Insertion

Abstract: SUMMARY: A total of 12 enterohemorrhagic Escherichia coli (EHEC) O157:H7 strains were isolated during a recent outbreak in a nursery school in Ehime Prefecture, Japan. These isolates were considered to be derived from a common strain when analyzed using an IS-printing method and pulsed-field gel electrophoresis. PCR analysis revealed that the isolates harbor stx 1 , stx 2 , eae, and hlyA. However, assessment of the production of the Stx proteins revealed that these isolates produced Stx1 but not Stx2. We deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A number of studies have demonstrated similar integration and excision into and out of stx genes (Asano et al , 2013; Park et al , 2013; Toro et al , 2015). Under certain conditions the loss of Stx prophages and Stx activity has been demonstrated, indicating that Stx activity may be a negative factor in certain cases and an advantage in others (Park et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated similar integration and excision into and out of stx genes (Asano et al , 2013; Park et al , 2013; Toro et al , 2015). Under certain conditions the loss of Stx prophages and Stx activity has been demonstrated, indicating that Stx activity may be a negative factor in certain cases and an advantage in others (Park et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…EHEC serotype O157:H7 is the most important pathogen in North America, the United Kingdom and Japan (Kaper et al, 2004). The pathogenic strain is so diverse in nature; twelve EHEC O157:H7 strains were isolated during a recent outbreak in a nursery school in Ehime Prefecture, Japan alone (Asano et al, 2013).…”
Section: Public Health Impact Of Ehecmentioning
confidence: 99%
“…Conclusion: These results suggest that absorption of VT2 from the intestine was inhibited by repeated administration of bovine immune colostral antibody against VT2 at early Introduction Food poisoning caused by Escherichia coli O157:H7 continues to occur in Japan. 1,2 Treatment for this type of infection generally does not involve antibiotics, 3e5 as verotoxin 2 (VT2) released from E. coli O157:H7 killed by antibiotics induces serious complications, such as hemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura, and brain damage. 6e8 The authors have reported the neutralizing efficacy of bovine immune colostral antibody against VT2 in mice and beagle dogs.…”
mentioning
confidence: 99%